Novel Reassortant Highly Pathogenic Avian Influenza A(H5N2) Virus in Broiler Chickens, Egypt - Hassan, Kareem E. (Emerg Infect Dis, 2020)
We detected a novel reassortant highly pathogenic avian influenza A(H5N2) virus in 3 poultry farms in Egypt. The virus carried genome segments of a pigeon H9N2 influenza virus detected in 2014, a nucleoprotein segment of contemporary chicken H9N2 viruses from Egypt, and hemagglutinin derived from the 2.3.4.4b H5N8 virus clade.